2009
DOI: 10.1248/bpb.32.1193
|View full text |Cite
|
Sign up to set email alerts
|

Risedronate Directly Inhibits Osteoclast Differentiation and Inflammatory Bone Loss

Abstract: Risedronate, a nitrogen-containing bisphosphonate, is widely used in the clinical field for the treatment of osteoporosis. Risedronate is known to exert its effects through binding to hydroxyapatite in bone tissue, inhibiting osteoclastic activity, and inducing apoptosis of osteoclasts. The purpose of this study was to determine the effects of risedronate on osteoclast differentiation in vitro and on an inflammatory bone loss model in vivo. Risedronate inhibited osteoclast differentiation in co-culture of bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 28 publications
3
22
0
8
Order By: Relevance
“…Brennan et al [37] have recently reported that osteoblasts played key roles in the mechanisms of action of SR with increased secretion of OPG and diminished RANKL availability, which led to stimulation of osteoblast differentiation and inhibition of osteoclast formation and resorption. However, bisphosphonates produced its antiresorptive effect on osteoclasts directly and intensively, resulting in significantly decrease of osteoclast formation and function, even leading to apoptosis of osteoclast [38,39]. However, special attention should be paid to the anabolic action of SR.…”
Section: Discussionmentioning
confidence: 99%
“…Brennan et al [37] have recently reported that osteoblasts played key roles in the mechanisms of action of SR with increased secretion of OPG and diminished RANKL availability, which led to stimulation of osteoblast differentiation and inhibition of osteoclast formation and resorption. However, bisphosphonates produced its antiresorptive effect on osteoclasts directly and intensively, resulting in significantly decrease of osteoclast formation and function, even leading to apoptosis of osteoclast [38,39]. However, special attention should be paid to the anabolic action of SR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study has shown that risedronate suppresses RANKL-induced osteoclastogenesis in co-cultures of mouse bone marrow cells (BMCs) with osteoblasts (Kwak et al 2009). Furthermore, fluorescent labeled risedronate analogs uptake by CD14-positive bone marrow monocytes such as osteoclast precursors (Roelofs et al 2010).…”
Section: Introductionmentioning
confidence: 91%
“…Bisphosphates are antiresorptive agents that have beneficial effects for the patients on preventing further bone loss, and their effects on increasing the bone mass is modest (Kwak et al, 2009, Yoshinari et al, 2002. It has been shown that bisphosphonate incorporated on to titanium implants increased bone density locally in the peri-implant region (Josse et al, 2005) with the effect of the antiresorptive drug limited to the vicinity of the implant.…”
Section: Bisphosphonatesmentioning
confidence: 99%